Postpartum Depression and Its Contributing Factors among Mothers during the COVID-19 Pandemic in North Jakarta, Indonesia - Venna Yaasmiin Aadillah; Irma Nurbaeti (Department of Nursing, Faculty of Medicine, Diponegoro University, 2023)
Background: Postpartum depression is a common psychological problem that occurs after birth. It has become especially prevalent in the era of the COVID-19 pandemic. Several factors contribute to postpartum depression. However, a limited study evaluated factors contributing postpartum depression among mothers during the COVID-19 pandemic, particularly in Indonesia.Purpose: This study aimed to explore postpartum depression among mothers and its contributing factors during the COVID-19 pandemic.Methods: This study adopted a cross-sectional design. A total of 110 postpartum mothers were recruited by accidental sampling with the following inclusion criteria: mothers between one month and one year after birth, married, a singleton birth and the baby alive, and the mother is healthy with no complications. The Edinburgh Postnatal Depression Scale was used to measure postpartum depression. Descriptive statistics, t-test, Fisher exact test, one-way ANOVA, and logistic regression were performed to analyze the data.Results: The prevalence of postpartum depression during the pandemic period was 31.82%. Factors contributing to postpartum depression were the mother’s age (p=0.011), childcare stress (p=0.001), stressful life events (p=0.003), and pregnancy status (p=0.0001). A logistic regression showed that pregnant status (Unplanned/unwanted pregnancy) was the most contributor to postpartum depression (β=0.377, t=5.138, p=0.0001).Conclusion: This study identified a high rate of postpartum depression with related factors, including mother’s age, childcare stress, life stress, and unplanned/ unwanted pregnancy. Screening for postpartum depression is required to ensure early detection among postpartum mothers.